2020
DOI: 10.1101/2020.06.14.20131102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detecting space-time clusters of COVID-19 in Brazil: mortality, inequality, socioeconomic vulnerability, and the relative risk of the disease in Brazilian municipalities

Abstract: The first case of COVID-19 in South America occurred in Brazil on February 25th, 2020. By June 7th, 2020, there were 691,758 confirmed cases, 36,455 confirmed deaths, and a mortality rate of 5.3%. To assist with the establishment of measures for the strategic planning to combat the COVID-19 pandemic in Brazil, we present the first Brazilian geographic study with the aims to examine active hand emerging space-time clusters of COVID-19. We examine the associations between clusters and mortality rate, vulnerabil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
(35 reference statements)
0
19
0
2
Order By: Relevance
“…A geographic study on active spatiotemporal clusters of COVID-19 conducted from February 25 th to June 7 th , 2020 in 5,570 Brazilian municipalities showed that one of the clusters was located in the Southeast region of Brazil covering the States of Minas Gerais, Espirito Santo and Rio de Janeiro. This cluster included 274 municipalities, 48 of which presented RR greater than 1.0 40 .…”
Section: Discussionmentioning
confidence: 99%
“…A geographic study on active spatiotemporal clusters of COVID-19 conducted from February 25 th to June 7 th , 2020 in 5,570 Brazilian municipalities showed that one of the clusters was located in the Southeast region of Brazil covering the States of Minas Gerais, Espirito Santo and Rio de Janeiro. This cluster included 274 municipalities, 48 of which presented RR greater than 1.0 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of cluster detections and analysis in COVID-19 pandemic is becoming useful nowadays as it detects active and emerging clusters of COVID-19 and notify epidemiologist, decision makers, and public health care officials, which can help in eradicating infections from affected sites, and improving interventions, quarantine, and isolation measures. The significant applications of clustering with respect to infectious diseases modelling are demonstrated across the world (Zarikas et al 2020 ), for example, India (Bhosale and Shinde 2020 ), USA (Desjardins et al 2020 ; Hohl et al 2020 ), Brazil (Martines et al 2020 ), Italy (Cereda et al 2020 ), China (Ji et al 2020 ; Liu et al 2020a , b ; Qiu et al 2020 ; Zhang et al 2020 ), Singapore (Bhosale and Shinde 2020 ; Pung et al 2020 ), South Korea (Shim et al 2020 ), French Alps (Danis et al 2020 ), Germany (Pfefferle et al 2020 ), Sergipe (Andrade et al 2020 ), etc.…”
Section: Infectious Diseases Modellingmentioning
confidence: 99%
“…Nesse sentido, o coeficiente de Gini é uma medida de distribuição de renda usada frequentemente para aferir desigualdade social. Estudos nos Estados Unidos e no Brasil demonstram que localidades com maiores coeficientes experienciam taxas mais elevadas de incidência por Covid-19, evidenciando que municípios mais desiguais exibem os maiores riscos da doença (Martines et al, 2020;Mukherji & Mukherji, 2020). Porém, a realidade social de Santa Catarina está distante da realidade brasileira.…”
Section: íNdice De Giniunclassified
“…Mesmo assim, a análise da pandemia Covid-19 por meio do aspecto da desigualdade social exige elementos suficientes para detalhar particularidades demográficas da população, como sexo, idade e etnia. E, nesse ponto, torna-se necessário que todos os estados brasileiros divulguem esses dados (Martines et al, 2020).…”
Section: íNdice De Giniunclassified